The Problem of Integration of Children with Disabilities in General Education Institutions - Minakova T. S., Mishina M. N. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2021)
this article presents an analysis of the problem of integration of children with disabilities in general education institutions, which they have to face in the process of their socialization and learning in new conditions, and outlines the main provisions of successful correctional and pedagogical work.
Keywords: интеграция; инклюзивное образование; integration; дети с ограниченными возможностями здоровья; inclusive education; общеобразовательные учреждения; children with disabilities; general education institutions